2020
DOI: 10.1021/acs.est.9b07773
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Metal Speciation in the Microenvironment Surrounding Phytoplankton Cells to Improve Predictions of Metal Bioavailability

Abstract: A lack of knowledge on metal speciation in the microenvironment surrounding phytoplankton cells (i.e., the phycosphere) represents an impediment to accurately predicting metal bioavailability. Phycosphere pH and O 2 concentrations from a diversity of algae species were compiled. For marine algae in the light, the average increases were 0.32 pH units and 0.17 mM O 2 in the phycosphere, whereas in the dark the average decreases were 0.10 pH units and 0.03 mM O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Siderophores can have a distinct non-classical function to take up metals other than Fe and play an important role as zincophores in rice soils. In line with recent findings 3 , 24 , 30 , 34 , 36 , 43 , 72 , the present study supports the conclusion that siderophores are central to access Zn in the soil.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Siderophores can have a distinct non-classical function to take up metals other than Fe and play an important role as zincophores in rice soils. In line with recent findings 3 , 24 , 30 , 34 , 36 , 43 , 72 , the present study supports the conclusion that siderophores are central to access Zn in the soil.…”
Section: Discussionsupporting
confidence: 93%
“…After the formation of a labile complex at the mineral surface, a ligand exchange reaction takes place in which the metal is transferred to a ligand with high Fe affinity and the low affinity ligand is free to react with the mineral again. Modelling and experimental studies of organic ligand complexation with a wide range of first row transition metals have demonstrated that pH and ionic strength exert a critical influence on the stability and lability of metal–ligand complexes 3 , 21 24 . The rhizosphere indeed is characterised by microscale gradients in pH and ionic strength, so it is reasonable to expect that these two master variables play a central part in synergistic roles of siderophores and other organic ligands during mobilisation and transport of zinc in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties include the proper evaluation of the interplay between the (i) bioavailability features of the metal species in the extracellular medium [10][11][12], (ii) metal biouptake flux at the biosensor surface, and (iii) kinetics of the intracellular biochemical reactions leading to photons emission [13,14]. In particular, items (i) and (ii) depend on the dynamics of metal ion speciation defined by the pertaining rate parameters for the formation and dissociation of metal complexes involving ionic, molecular and/or particulate metal ligands dispersed in solution [12,15,16]. In turn, these rate constants, together with the diffusion properties of the various metal forms, determine the lability of the complexed metal species, i.e., their contribution to the dynamic supply of free metals to the biosensor surface [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Precise quantification of chemical conditions in the phycosphere is crucial for better understanding how phytoplankton will respond to environmental changes. Evidence is emerging that interactions between phytoplankton and abiotic/biotic environments are governed by micro-and nano-scale interfacial processes [13,47,49,50], which cannot be determined using bulk water analyses. Small changes in the phycosphere likely translate into large impacts on the oceanic carbon and nitrogen cycle (Fig.…”
Section: Consequences Of Phycosphere Ph Change For Fe Speciation and ...mentioning
confidence: 99%
“…Ocean acidification will also affect calcium carbonate production and may drive distinct malformations of coccolith structures for calcifying phytoplankton species [9]. However, pH conditions in the micro-scale region surrounding phytoplankton cells can differ markedly from ambient bulk seawater, as observed in giant diatoms and algal colonies [10][11][12][13]. The microenvironment, known as the phycosphere [14], is the unstirred boundary layer in the immediate vicinity of an algal cell, where the effects of algal metabolisms and other associated microorganisms can be significant.…”
Section: Introductionmentioning
confidence: 99%